A review：Modified biochar as an adsorbent for phosphorus removal from water - Tian, Aodi; Huang, He; Zhang, Xulin; Htet, Hein Min; Hu, Zhaofeng; Zhang, Haozhen (International Journal of Scientific Research and Management (IJSRM), 2024)
In recent years,eutrophication of water bodies has become increasingly severe due to the rising content of phosphorus in these bodies.This escalation adversely affects the normal growth of aquatic organisms,leading to the deterioration of water quality,and ultimately impacting human life.Phosphorus removal is a crucial direction for addressing water body pollution.Therefore,it is of utmost importance to identify efficient,affordable,and feasible methods for removing phosphorus from wastewater.Adsorption,owing to its simplicity,efficiency,and low cost,is widely employed in water treatment.Biochar,in particular,is extensively used due to its high efficiency,renewability,low cost,and the ready availability of raw materials.This paper reviews the preparation methods of biochar and modified biochar,analyses the effects of pyrolysis temperature,solution pH,reaction temperature,adsorbent dosage,adsorption time and co-existing ions on the phosphorus removal of biochar materials.It also explores the necessity of desorption and regeneration of biochar,along with the prospects of biochar in the future of phosphorus removal.